AB1133 High consumption of seafoods or vegetables negatively correlates with disease activity of rheumatoid arthritis. (15th June 2017) - Murakami, I; Murakami, K; Hashimoto, M; Torii, M; Ikeda, K; Kuwabara, A; Tanaka, K; Yoshida, A; Usui, T; Kuramoto, N; Nakashima, R; Imura, Y; et al.
Abstract : Background: Food intake is one of the important environmental factors of various diseases, and possibly influences the pathogenesis of RA. However, we have little knowledge about the impact of food intake on the pathogenesis of RA. Because each country has its own food culture, the study focused on the dietary habit in Japan is essential in order to clarify the clinical impact of food intake in Japanese RA patients. Objectives: The aim of this study is to clarify the relationship between the dietary habit of RA patients and their disease status. Methods: We took the questionnaire survey about dietary habit in 2015, in KURAMA (Kyoto University Rheumatoid Arthritis Management Alliance) cohort as single institute. Disease activity was also examined in this cohort. These data were combined and statistically analyzed. Results: 563 RA patients were enrolled from KURAMA cohort; female: male 4:1, age 63 years old, disease duration 15.5 years, DAS28-ESR 2.8 on average. Multivariate analysis showed that the intake frequency of vegetables had statistically significant negative correlation with DAS28-ESR (β=−0.17, p<0.01), SDAI (β=−0.15, p<0.01), HAQ (β=−0.15, p<0.01) and MMP-3 (β=−0.13, p<0.01). The intake frequency of frozen foods had positive correlation with MMP-3 (β=0.12, p<0.01). The intake frequency of juice had positive correlation with DAS28-ESR (β=0.11, p<0.01) and SDAI (β=0.11, p<0.01). Factor analysis revealed five dietary patterns, which were labeled "seafoods", "meat and fried foods", "vegetables and fruits", "snacks" and "processed foods". The "seafoods" had statistically significant negative correlation with DAS28-ESR (β=−0.10, p=0.027), SDAI (β=−0.11, p=0.015), HAQ (β=−0.11, p=0.015) and MMP-3 (β=−0.11, p=0.013). The "vegetables and fruits" had also statistically significant negative correlation with DAS28-ESR (β=−0.13, p<0.01), SDAI (β=−0.14, p=0.015), HAQ (β=−0.17, p<0.001) and MMP-3 (β=−0.14, p<0.01). Conclusions: This study implicates that the disease activity of RA may be alleviated by high consumption of vegetables and fruits, or seafoods. Disclosure of Interest: None declared